The Degree of Availability of Professional Teaching Competencies for Physical Education Teachers in Jordan - Mohammad AL-Momani; Randa Saleh Jawarneh (Universitas Singaperbangsa Karawang, 2022)
The study aimed to identify the degree of availability of professional teaching competencies for physical education teachers in Jordan from their point of view and its relationship to some variables such as gender, academic qualification and years of experience. The study sample consisted of (784) male and female teachers in the second semester of the year (2021/2022); The study concluded that the degree of availability of professional teaching competencies was moderately in all fields of study, in addition to the absence of statistically significant differences that are attributed to the variables of gender and educational qualification, and the presence of statistically significant differences due to the variable years of experience and in favor of teachers with experience of more than 10 years. .